Multi-directional Wind Turbine System Optimisation and Mathematical Modelling for India’s Sustainable Wind Energy Development - Dr. Ashis Acharjee; Jhunaan Chakma; Subhajit Das Chowdhury; Ananyajoy Chakma; Madhujit Deb (International Journal of Mechanical Dynamics and Systems Analysis, 2023)
The global trend towards green energy usage is expanding. Wind power is clean and sustainable and may compete with fossil fuels in the electricity market. This project's manufacturing cost must match fossil fuels or other energy sources to be competitive. The main investment in wind generation is in machinery and infrastructure. Wind power becomes competitive by lowering energy costs through turbine design, building, and operation. Understanding wind turbine activity over its operational range requires an accurate mathematical model. This model allows complex control algorithms to optimize wind turbine operation. Modelling controls wind turbine performance. This study investigates the power coefficient parameter to meet wind turbine model goals. Next-generation turbine designers and researchers will benefit from model results. This information can optimize turbine design and lower generation costs, lowering wind energy expenses. This will make wind energy a profitable choice.
Keywords: Wind speed; blade speed ratio; efficiency; electrical generator; power grid; turbine output